Progesterone Receptor Induces ErbB-2 Nuclear Translocation To Promote Breast Cancer Growth via a Novel Transcriptional Effect: ErbB-2 Function as a Coactivator of Stat3 - Beguelin, Wendy (2010)
Progesterone receptor (PR) and ErbB-2 bidirectional cross talk participates in breast cancer development. Here, we identified a new mechanism of the PR and ErbB-2 interaction involving the PR induction of ErbB-2 nuclear translocation and the assembly of a transcriptional complex in which ErbB-2 acts as a coactivator of Stat3. We also highlighted that the function of ErbB-2 as a Stat3 coactivator drives progestin-induced cyclin D1 promoter activation. Notably, PR is also recruited together with Stat3 and ErbB-2 to the cyclin D1 promoter, unraveling a new and unexpected nonclassical PR genomic mechanism. The assembly of the nuclear Stat3/ErbB-2 transcriptional complex plays a key role in the proliferation of breast tumors with functional PR and ErbB-2. Our findings reveal a novel therapeutic intervention for PR- and ErbB-2-positive breast tumors via the specific blockage of ErbB-2 nuclear translocation.